2014
DOI: 10.1371/journal.pone.0102714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Use, Topography and Socio-Economic Factors on River Water Quality in a Mountainous Watershed with Intensive Agricultural Production in East China

Abstract: Understanding the primary effects of anthropogenic activities and natural factors on river water quality is important in the study and efficient management of water resources. In this study, analysis of Variance (ANOVA), Principal component analysis (PCA), Pearson correlations, Multiple regression analysis (MRA) and Redundancy analysis (RDA) were applied as an integrated approach in a GIS environment to explore the temporal and spatial variations in river water quality and to estimate the influence of watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 44 publications
1
80
3
1
Order By: Relevance
“…The positive and negative relationships between AG and TN, TP and NH 4 + -N in GWR analysis (Figs.4, 5 and 8) showed divergence from our OLS results (Table 2) and other studies using traditional global statistical methods (e.g., Seeboonruang, 2012;Wang et al, 2014;Wan et al, 2014;Chen and Lu, 2014). In these studies, AG had a strong positive effect on a b water pollution indicators because agricultural activities, such as fertilizer and pesticide application and livestock farming, are often the main non-point pollution source.…”
Section: Interpretation Of Water Quality and Predicting Variablescontrasting
confidence: 98%
See 1 more Smart Citation
“…The positive and negative relationships between AG and TN, TP and NH 4 + -N in GWR analysis (Figs.4, 5 and 8) showed divergence from our OLS results (Table 2) and other studies using traditional global statistical methods (e.g., Seeboonruang, 2012;Wang et al, 2014;Wan et al, 2014;Chen and Lu, 2014). In these studies, AG had a strong positive effect on a b water pollution indicators because agricultural activities, such as fertilizer and pesticide application and livestock farming, are often the main non-point pollution source.…”
Section: Interpretation Of Water Quality and Predicting Variablescontrasting
confidence: 98%
“…As an important regulator of pollutants in overland flow and interflow, land use/land cover has become a critical research topic for elucidating the relationship between surface water quality and non-point source pollutants. Several statistical methods are widely used in these studies, such as correlation analysis, cluster analysis, principal component analysis, linear regression models, linear mixed effects models and exponential models Wan et al, 2014;Chen and Lu, 2014;Seeboonruang, 2012;Ahearn et al, 2005;Madrinan et al, 2012). Previous results often show that land-use types closely related to human activities, such as agriculture and urban, were positively correlated with river pollution indicators (e.g., nitrogen, phosphorus, ammonia), while woodlands and grasslands that were less affected by human activities had negative correlations.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Are there seasonal differences in the impacts of land use on water quality? (3) What are the implications of our findings for managing and mitigating pollutant loadings?…”
mentioning
confidence: 99%
“…The record of SBC showed that all of the cases occurred near the watersheds (figure 3). Watershed is an important component for the rice field, and the water quality is strongly affected the socio-economic condition of society living near the area [22]. Therefore, most of the agricultural and the settlement area are located near the watershed.…”
Section: Green Corridor As a Natural Highwaymentioning
confidence: 99%